Diagnostic Value of Right Pulmonary Artery Distensibility Index in Dogs with Pulmonary Hypertension: Comparison with Doppler Echocardiographic Estimates of Pulmonary Arterial Pressure. (19th February 2016) - Visser, L.C.; Im, M.K.; Johnson, L.R.; Stern, J.A.
Abstract : Background: Noninvasive diagnosis of pulmonary hypertension (PH) primarily relies upon Doppler echocardiography of tricuspid regurgitation (TR). However, TR might be absent or difficult to measure. Hypothesis/Objectives: To determine the diagnostic value of right pulmonary artery distensibility (RPAD) index for prediction of Doppler‐derived estimates of pulmonary artery (PA) pressure compared to other indices of PH in dogs. Animals: Sixty‐nine client‐owned dogs with TR. Methods: Prospective observational study. Dogs were allocated to groups according to TR pressure gradient (TRPG): TRPG <36 mmHg (control, n = 22), TRPG 36–50 (n = 16), TRPG 50–75 (n = 14) and TRPG >75 mmHg (n = 17). Right pulmonary artery distensibility index, acceleration time to peak PA flow (AT), AT: ejection time of PA flow (AT:ET) and main PA size: aorta size (MPA:Ao) were calculated in each dog. Results: Right pulmonary artery distensibility index demonstrated the strongest correlation ( r = −0.90; P < .0001) to TRPG followed by MPA:Ao ( r = 0.78; P < .0001), AT ( r = −0.69; P < .0001) and AT:ET ( r = −0.68; P < .0001). RPAD index possessed the most accurate cutoff (<29.5%; Sensitivity [Sn] 0.84, Specificity [Sp] 0.95) to predict TRPG >50 mmHg compared to AT (<53.9 ms; Sn 0.74, Sp 0.87), AT:ET (<0.30; Sn 0.61, Sp 0.97) and MPA:Ao (>1.04; Sn 0.94, Sp 0.74). All intra‐ and interobserver measurement variabilities exhibited coefficients of variation ≤13%. Conclusions and Clinical Importance: Right pulmonary artery distensibility index is an accurate predictor of TRPG and should be particularly useful if TR is absent or difficult to measure.